Innate Lymphoid Cells in Human Pregnancy - Mendes, João; Areia, Ana Luísa; Rodrigues-Santos, Paulo; Santos-Rosa, Manuel; Mota-Pinto, Anabela (Frontiers in Immunology, 2020)
Innate Lymphoid Cells (ILCs) are a new set of cells considered a part of the innate immune system. ILCs are classified in five subsets (according to their transcription factors and cytokine profile) as Natural Killer Cells (NK cells); group 1 ILCs; group 2 ILCs; group 3 ILCs and Lymphoid tissue inducers (LTi). Functionally, these cells resemble T helper population but lack the expression of recombinant genes, which is essential for the formation of T cell receptor. In this work, the authors address the distinction between peripheral NK cells and decidual NK cells, highlighting their diversity in ILC biology ant its relevance to human pregnancy. ILCs are effector cells important in promoting immunity, inflammation and tissue repair. Recent studies have directed their attention to ILC actions in pregnancy. Dysregulation or expansion of pro-inflammatory ILCs populations, as well as abnormal tolerogenic responses, may directly interfere with pregnancy ultimately resulting in pregnancy loss or adverse outcomes. In this review, we will characterize these cells considering recent findings, and addressing knowledge gaps in perinatal medicine in the context of ILCs biology. Moreover, we will discuss the relevance of these cells not only to the process of immune tolerance but also in disease.